Spatial pattern of SuStainable urban Development inDicator for the montreal urban community - Amin, Shohel Reza; Tamima, Umma (Journal of Architecture and Urbanism, 2015)
The City of Montreal initiated a First Strategic Plan for Sustainable Development in 2005 followed by a Community and Corporate Sustainable Development Plan in 2010–2015. This study proposes a sustainable urban development indicator (SUDI) for each Montreal Urban Community (MUC) to evaluate the achievements of sustainable development plans. This study identifies thirty-two variables as the attributes of sustainable urban development. The multivariate technique and Exploratory Spatial Data Analysis are applied to determine the spatial pattern of SUDI for each MUC. The spatial pattern of SUDI identifies that Ville Marie, Verdun, Sud-Ouest, Mercier-Hochelaga-Maisonneuve and Plateau Mont-Royal have strong sustainable development. The findings of this study help the City of Montreal to understand the improvement of the sustainable development plans for Montreal city and to distribute the municipal budget for the community benefits accordingly.